2018
DOI: 10.1111/cas.13857
|View full text |Cite
|
Sign up to set email alerts
|

Silencing circular RNA UVRAG inhibits bladder cancer growth and metastasis by targeting the microRNA‐223/fibroblast growth factor receptor 2 axis

Abstract: Circular RNA UVRAG (circUVRAG), a type of non‐coding RNA, is derived and cyclized by part of the exon from the UVRAG gene. However, the role of circUVRAG in bladder cancer (BLCA) has not been reported. The purpose of the present study was therefore to characterize the role of circUVRAG in BLCA. Bioinformatics analysis showed interactive relationships among circUVRAG, microRNA‐223 (miR‐223), and fibroblast growth factor receptor 2 (FGFR2). Quantitative real‐time PCR was used to detect the expression of circUVRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…In this study, we analyzed human circRNA microarray data and found for the first time that hsa_circ_0023642 is expressed in higher levels in GC than in adjacent non‐tumor tissues. It has been reported in the literature that silencing circular RNA UVRAG (also known as Hsa_circ_0023642) inhibited bladder cancer growth and metastasis by targeting the miR‐223/FGFR2 axis 13,14 . However, compared with the study in bladder cancer, the level of expression and function of hsa_circ_0023642 in GC development are still largely unknown, and the target genes we have done were different.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, we analyzed human circRNA microarray data and found for the first time that hsa_circ_0023642 is expressed in higher levels in GC than in adjacent non‐tumor tissues. It has been reported in the literature that silencing circular RNA UVRAG (also known as Hsa_circ_0023642) inhibited bladder cancer growth and metastasis by targeting the miR‐223/FGFR2 axis 13,14 . However, compared with the study in bladder cancer, the level of expression and function of hsa_circ_0023642 in GC development are still largely unknown, and the target genes we have done were different.…”
Section: Discussionmentioning
confidence: 92%
“…[10][11][12][13]. Particularly, miR-223 presents ectopic expression in different urogenital cancers such as bladder cancer [14], renal carcinoma [15] and testicular tumors [16]. The current advances of its role in cancers have been summarized in a recent review [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because of their covalently closed-structure, circRNAs are more stable and more suitable as efficacious biomarkers than linear-RNAs, such as lncRNAs and miRNAs [20]. For instance, circ_UVRAG [21], circ_BACH2 [22] and circ_ANKS1B [23] have been identified to be diagnostic or prognostic biomarker for gastric cancer, papillary thyroid carcinoma and breast cancer, respectively. Previous report has been demonstrated that hsa_circ_0027345 (a circRNA derived from linear LRIG3) was overexpressed in HCC tissues [11].…”
Section: Discussionmentioning
confidence: 99%